Age Criteria As Operative Mortality Predictor After Modified Blalock-Taussig Shunt - muammar riyandi; oktavia lilyasari; dafsah arifa juzar; budi rahmat (Jurnal Kardiologi Indonesia, 2019)
Background: Modified Blalock-Taussig shunt (MBTS) is considered as a simple procedure but has a considerable operative mortality rate. Patient’s characteristics who underwent MBTS in Indonesia is quite different than other country. There was no predictor of operative mortality has been identified in Indonesian.Objectives: To compare mortality rate based on age criteria and to identify mortality and morbidity predictors after MBTS procedure.Methods: A retrospectively cohort study was conducted on 400 patients who underwent MBTS at National cardiovascular center Harapan Kita (NCCHK) between January 2013 and december 2017.Results: There were 32,1% death at age ≤ 28 days, 19,9% at age 29-365 days, 3,6% at age 366-1825 days and 8% at age > 1825 days. Body weight < 3 kg, haematocrite level > 45% before procedure and activated partial thromboplastine time level (aPTT) < 60 seconds were operative mortality  predictors. Postoperative morbidity rate was 32,9%. Packed red cell  transfusion (PRC) more than 6 ml/kg, mechanical ventilator use before procedure, prostaglandin E1 use before procedure, aPTT level less than 60 seconds after procedure were identified as postoperative morbidity predictors.Conclusion: Operative mortality rate significantly different among age criteria but it was not proven as an operative mortality predictors. Body weight < 3 kg increase mortality rate and haematocrite level higher than 45% and aPTT level less than 60 seconds decrease mortality rate. Postoperative morbidity predictors were PRC transfusion more than 6ml/kg, mechanical ventilator use before procedure, prostaglandine E1 use and aPTT level less than 60 seconds.